2019
DOI: 10.30699/fhi.v8i1.189
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Seeking Behavior (HISB) among the University Students

Abstract: Introduction: Understanding the information seeking behavior of individuals, especially students who are more likely to seek health information than other people, can be seen as an opportunity to provide resources to improve lifestyle or prevent possible health threatening behaviors among students. The main objective of this research is to determine the HISB among students of Tabriz University of Medical Sciences (TUOMS).Material and Methods: This descriptive cross-sectional study was carried out at TUOMS amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Another study on the students aged 15-18 years from different schools in Isfahan [27], a study involving 430 students from Gonabad University [42], two other studies at Gorgan and Kermanshah universities [29,43], Two other studies at Tabriz University and Tehran University of Medical Sciences have also have reported the similar results [24,44].…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Another study on the students aged 15-18 years from different schools in Isfahan [27], a study involving 430 students from Gonabad University [42], two other studies at Gorgan and Kermanshah universities [29,43], Two other studies at Tabriz University and Tehran University of Medical Sciences have also have reported the similar results [24,44].…”
Section: Resultsmentioning
confidence: 81%
“…Adolescents often seek health information with different objectives and motives [28,29,44] and they, typically seek information relating to the variety of health subjects such as healthy eating, physical activity, exercise, weight control, risks and complications of diseases treatments, sexual and reproductive health, sexual and physical abuse, alcohol consumption and other substances, tobacco use, mental health, accidents and injuries, health care providers and support groups [27,33,35,38,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two other studies in Tehran high schools have reported similar rates [37,38]. Another study on students aged 15-18 years from different schools in Isfahan [21], a study involving 430 students from Gonabad University [39], two other studies at Gorgan and Kermanshah universities [40,41], and two other studies at Tabriz University and Tehran University of Medical Sciences have reported similar results [19,42].…”
Section: Principal Findingsmentioning
confidence: 77%